MANAGEMENT OF AQUATIC ECOSYSTEM BASED LOCAL SOCIETY’S KNOWLEDGE: A CASE STUDY OF IKAN LARANGAN IN PANDAM GADANG, WEST SUMATERA, INDONESIA - Ilhami, Aldeva; ., Riandi (PEOPLE: International Journal of Social Sciences, 2018)
Minangkabau community is a majority ethnic lived in the West Sumatra province. We can find a local wisdom in this province related to environmental conservation such as ikan larangan. it is part of river to be forbidden area to fish within certain limits and span of time. The researchers interested to discover it which is located in Pandam Gadang village, West Sumatera province. The aims of research is to explore the local wisdom of ikan larangan which is located in Pandam Gadang village and to analyze conservation values contained it. We use interview, observation and documentation are used to collect data. Respondents involved in this research are elders and people in the community purposively. The results showed that the local community made a part of river as ikan larangan divided 3 zones and those areas have conservation values such as protection, preservation and sustainable use.